Suppression of Heterogeneous Nuclear Ribonucleoprotein C Inhibit Hepatocellular Carcinoma Proliferation, Migration, and Invasion via Ras/MAPK Signaling Pathway - Hu, Jiejun; Cai, Dong; Zhao, Zhibo; Zhong, Guo-Chao; Gong, Jianping (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC), the most common malignant tumor, has high fatality and recurrence rates. Accumulating evidence shows that heterogeneous nuclear ribonucleoprotein C (HNRNPC), which is mainly involved in RNA splicing, export, and translation, promotes progression and metastasis of multiple tumor types; however, the effects of HNRNPC in HCC are unknown. In the present study, high levels of HNRNPC were detected in tumor tissues compared with para-tumor tissues by immunohistochemical and western blot assays. Furthermore, Cox proportional hazards regression models, the Kaplan–Meier method, and clinicopathologic features analysis showed that HNRNPC was not only an independent prognostic factor for both overall and disease-free survival in HCC but also a predictor of large tumor size and advanced tumor stage. Functional experiments revealed that silencing of HNRNPC not only led to arrest of more HCC cells at G0/G1 phase to inhibit their proliferation, but also suppressed EMT process to block their invasion, and migration in vitro; this was related to the Ras/MAPK signaling pathway. In addition, blocking of HCC cell proliferation regulated by HNRNPC silencing was observed in vivo. Finally, rescue tests showed that after recovery of Ras/MAPK signaling pathway activity by treatment with Ras agonists, the proliferation, migration, and invasion suppression of Huh-7 and Hep 3B cell lines caused by HNRNPC knockdown was partially reversed. Taken together, these results indicate that HNRNPC knockdown inhibits HCC cell proliferation, migration and invasion, in part via the Ras/MAPK signaling pathway. Thus, HNRNPC may have an important role in the progression of HCC and represents a promising biomarker for evaluation of prognosis and a potential therapeutic target in HCC patients.